Association between intravenous thrombolysis and clinical outcomes among patients with ischemic stroke and unsuccessful mechanical reperfusion - Faizy, Tobias D.; Broocks, Gabriel; Heit, Jeremy J.; Kniep, Helge; Flottmann, Fabian; Meyer, Lukas; Sporns, Peter; Hanning, Uta; Kaesmacher, Johannes; Deb-Chatterji, Milani; Vollmuth, Philipp; Lansberg, Maarten G.; et al. (JAMA network open, 2023)
Clinical evidence of the potential treatment benefit of intravenous thrombolysis preceding unsuccessful mechanical thrombectomy (MT) is scarce.To determine whether intravenous thrombolysis (IVT) prior to unsuccessful MT improves functional outcomes in patients with acute ischemic stroke.Patients were enrolled in this retrospective cohort study from the prospective, observational, multicenter German Stroke Registry-Endovascular Treatment between May 1, 2015, and December 31, 2021. This study compared IVT plus MT vs MT alone in patients with acute ischemic stroke due to anterior circulation large-vessel occlusion in whom mechanical reperfusion was unsuccessful. Unsuccessful mechanical reperfusion was defined as failed (final modified Thrombolysis in Cerebral Infarction grade of 0 or 1) or partial (grade 2a). Patients meeting the inclusion criteria were matched by treatment group using 1:1 propensity score matching.Mechanical thrombectomy with or without IVT.Primary outcome was functional independence at 90 days, defined as a modified Rankin Scale score of 0 to 2. Safety outcomes were the occurrence of symptomatic intracranial hemorrhage and death.After matching, 746 patients were compared by treatment arms (median age, 78 [IQR, 68-84] years; 438 women [58.7%]). The proportion of patients who were functionally independent at 90 days was 68 of 373 (18.2%) in the IVT plus MT and 42 of 373 (11.3%) in the MT alone group (adjusted odds ratio [AOR], 2.63 [95% CI, 1.41-5.11]; P = .003). There was a shift toward better functional outcomes on the modified Rankin Scale favoring IVT plus MT (adjusted common OR, 1.98 [95% CI, 1.35-2.92]; P < .001). The treatment benefit of IVT was greater in patients with partial reperfusion compared with failed reperfusion. There was no difference in symptomatic intracranial hemorrhages between treatment groups (AOR, 0.71 [95% CI, 0.29-1.81]; P = .45), while the death rate was lower after IVT plus MT (AOR, 0.54 [95% CI, 0.34-0.86]; P = .01).These findings suggest that prior IVT was safe and improved functional outcomes at 90 days. Partial reperfusion was associated with a greater treatment benefit of IVT, indicating a positive interaction between IVT and MT. These results support current guidelines that all eligible patients with stroke should receive IVT before MT and add a new perspective to the debate on noninferiority of combined stroke treatment.
Gesehen am 07.11.2023